WHY CHINESE ARE THINKING DIFFERENTLY? (CULTURAL AND NEUROLOGICAL CASE-STUDY) - Maria Butucea (European Scientific Journal, ESJ, 2014)
Are Chinese students using different ―mental program‖? Have their performances natural causes or educational causes? The goal of the present article was to investigate the neural correlates of Chinese mind-brain and how it works and notice the importance of all these for education. We were focused in some relation between language, mathematic and music as activities and try to find scientific explanations at the brain‘s functional level. We were particularly interested in awareness of educationist about the role of cultural background to improve semantic memory in their teaching. We try to show some recent outcomes of neurosciences studies about functional locations and brain‘s areas that are mostly activated during accomplishing different tasks. Educationists already empirically knew that children like music and also teachers insist on semantic memory in their teaching, but they lack the scientific explanation of the process and how important could be the results of neurosciences researches for their activities [10].